ROLE OF HIGH RESOLUTION COMPUTED TOMOGRAPHY IN THE EVALUATION OF TEMPORAL BONE LESIONS - PALLAVI, NADIKOTA; SOWMYA, RAMARAPPU (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The study’s primary goal is to assess inflammatory, traumatic, and neoplastic disorders that impact the temporal bone using high resolution computed tomography (HRCT). The other aim is to comprehend how HRCT can diagnose and detect pathologies of the temporal bone. Methods: The study was conducted at Dr. Patnam Mahender Reddy Institute of Medical Sciences from Jan 2018 to Jan 2020 with a sample size of 60. Written consent for participation in the study was taken before the scan. The study was evaluated with multidetector HRCT-HITACHI 128 SLICE machine. CT images are usually acquired or displayed in axial and coronal planes. Results: Among 60 patients, 44 patients were diagnosed with infections, 11 were diagnosed with tumors, and five patients with anatomical variants. Among 60 patients, 32 (53.3%) were male patients, and 28 (46.6%) were female patients; hence, study shows a male preponderance. Out of 60 patients, the highest number was recorded in those aged 21–30 years 16 (36%). Among 60 patients, 44 suspected of having a middle ear infection were studied. Among these 44 patients, 27 (61.3%) were diagnosed with otomastoiditis, 16 (36%) patients were diagnosed with cholesteatoma, and 1 (2.2%) patient was diagnosed with malignant otitis externa. In our study population of 60 patients, 11 were diagnosed with neoplasms. Among the 11 patients, 7 (67%) were diagnosed with acoustic neuroma in the cerebellopontine angle. Conclusion: The existence of cholesteatoma, changes to the ossicular chain, and erosion of the lateral semicircular canal were all intraoperatively detected in the present study with excellent sensitivity to the clinical and radiographic findings. For correcting any congenital ear anomalies, the HRCT results were helpful for planning and management tools for the surgeon.